2011
DOI: 10.4028/www.scientific.net/amr.280.13
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Corrosion Resistance of Manganese Slag Cement Stabilized Macadam Base

Abstract: In this study, the unconfined compressive strength and anti-corrosion capacity and erosion resistibility were evaluated. Different admixture amounts of manganese slag cement were used as constituents of stabilized macadam base specimens. On the prepared specimens mechanical property test、continuous immersion experiment and anti erosion experiment were carried out for the research on the corrosion resistance of manganese slag cement stabilized macadam base. It was observed that corrosion resistance and scour re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…To find methods of improving the erosion resistance of the subgrade, studies have researched how the strength of the subgrade filler could be improved and how eroding tests could be optimized according to the actual situation of the subgrade and have proposed antierosion measures. In particular, extensive attention has been paid to efforts that seek to improve the strength of subgrade materials, and some chemical binders, such as cement [1][2][3][4], lime [5], nano-MgO [6], coal ash [7], fiber [8], marine-dredged soil [9], sustainable regenerated binding materials [10], and manganese slag [11], have been applied to the subgrade to investigate their effect on the water stability and the erosion resistance of the soil subgrade. Researchers at home and abroad have found that using the aforementioned materials (especially cement) not only greatly increases the strength of the subgrade, but also additionally improves the water damage resistance.…”
Section: Introductionmentioning
confidence: 99%
“…To find methods of improving the erosion resistance of the subgrade, studies have researched how the strength of the subgrade filler could be improved and how eroding tests could be optimized according to the actual situation of the subgrade and have proposed antierosion measures. In particular, extensive attention has been paid to efforts that seek to improve the strength of subgrade materials, and some chemical binders, such as cement [1][2][3][4], lime [5], nano-MgO [6], coal ash [7], fiber [8], marine-dredged soil [9], sustainable regenerated binding materials [10], and manganese slag [11], have been applied to the subgrade to investigate their effect on the water stability and the erosion resistance of the soil subgrade. Researchers at home and abroad have found that using the aforementioned materials (especially cement) not only greatly increases the strength of the subgrade, but also additionally improves the water damage resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the performance analysis, it is recommended that the dosage of BAA is 20% to 30%. Qin et al [32] evaluated the corrosion resistance of manganese slag cement-stabilized macadam base. It was observed that corrosion resistance and scour resistance performances were significantly improved with the incorporation of manganese.…”
Section: Introductionmentioning
confidence: 99%